2004
DOI: 10.1152/ajpendo.00384.2003
|View full text |Cite
|
Sign up to set email alerts
|

Exercise augments the acute anabolic effects of intradialytic parenteral nutrition in chronic hemodialysis patients

Abstract: Exercise augments the acute anabolic effects of intradialytic parenteral nutrition in chronic hemodialysis patients. Am J Physiol Endocrinol Metab 286: E589-E597, 2004. First published December 16, 2003 10.1152/ajpendo.00384.2003.-Decreased dietary protein intake and hemodialysis (HD)-associated protein catabolism are among several factors that predispose chronic hemodialysis (CHD) patients to uremic malnutrition and associated muscle wasting. Intradialytic parenteral nutrition (IDPN) acutely reverses the net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
61
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 47 publications
1
61
1
Order By: Relevance
“…Analyses were conducted as part of a study from which data on whole body and muscle protein homeostasis have already been reported (Pupim et al, 2004b). Out of the six subjects previously recruited (Pupim et al, 2004b), five (46719 years old, four males, four blacks) had information on FSR available for analysis and were included in this study.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Analyses were conducted as part of a study from which data on whole body and muscle protein homeostasis have already been reported (Pupim et al, 2004b). Out of the six subjects previously recruited (Pupim et al, 2004b), five (46719 years old, four males, four blacks) had information on FSR available for analysis and were included in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Out of the six subjects previously recruited (Pupim et al, 2004b), five (46719 years old, four males, four blacks) had information on FSR available for analysis and were included in this study. Inclusion criteria consisted of patients on a thrice-weekly CHD program for more than 6 months, using a biocompatible hemodialysis membrane (Fresenius F80) and an adequate dose of dialysis (single pool Kt/V41.4).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations